2011
DOI: 10.1111/j.1365-2982.2011.01707.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol consumption induces an overproduction of NO by nNOS- and iNOS-expressing myenteric neurons in the murine small intestine

Abstract: Chronic alcohol consumption induces a marked increase in NO synthesis by jejunal myenteric neurons, accompanied by an up-regulation of iNOS-expressing neurons and a downregulation of nNOS neurons. We conclude that the overproduction of NO may be a direct cause of gastrointestinal motility disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
(127 reference statements)
1
20
1
1
Order By: Relevance
“…Participation of Ca þ þ -independent NOS, such as iNOS, is also possible (Starkey et al, 2001). Spontaneous NO release from the guinea pig ileum, human colon and mouse ileum involves both nNOS and iNOS (LePard, 2005;Bagyánski et al, 2011;Giaroni et al, 2013). It is, thus, possible that, in guinea pig ileum, NMDA receptors modulate NO production from myenteric neurons by activating both nNOS and iNOS.…”
Section: Discussionmentioning
confidence: 94%
“…Participation of Ca þ þ -independent NOS, such as iNOS, is also possible (Starkey et al, 2001). Spontaneous NO release from the guinea pig ileum, human colon and mouse ileum involves both nNOS and iNOS (LePard, 2005;Bagyánski et al, 2011;Giaroni et al, 2013). It is, thus, possible that, in guinea pig ileum, NMDA receptors modulate NO production from myenteric neurons by activating both nNOS and iNOS.…”
Section: Discussionmentioning
confidence: 94%
“…Given the evidence that nNOS has a protective role on the heart (Zhang and Casadei, 2012), our results suggest that a decrease in nNOS levels could be the mechanism underlying the adverse remodeling of the LV in rats exposed to chronic ethanol consumption. The effects of ethanol on different cells or organs are not the same, and these differences seem to depend on the NOS isoform involved (Bagyánszki et al, 2011;Deng and Deitrich, 2007;Husain et al, 2008;Khanna et al, 2007). On this matter, it has been shown that both myocardial dysfunction and blunted adrenergic signaling induced by 4 weeks of ethanol intake were related with an increase in inducible NOS (iNOS) isoform (Khanna et al, 2007).…”
Section: Discussionmentioning
confidence: 95%
“…On this matter, it has been shown that both myocardial dysfunction and blunted adrenergic signaling induced by 4 weeks of ethanol intake were related with an increase in inducible NOS (iNOS) isoform (Khanna et al, 2007). In the rat myenteric neurons, 5 weeks of ethanol consumption induced an up-regulation of iNOS while nNOS-expressing neurons were downregulated (Bagyánszki et al, 2011), and there were no changes in nNOS immunoreactivity in the corpus striatum after 6 weeks of ethanol consumption (Evrard et al, 2006). Our results also show that the ethanolinduced reduction in nNOS protein levels was due, in part at least, to a decrease in the expression of nNOS by cardiomyocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Various reports have described the plastic remodeling of the nitrergic neurons during development [55,58,59] , aging [60] and pathological conditions [22,61] . Several studies have suggested that nitrergic myenteric neurons are especially susceptible to the development of neuropathy in digestive tract diseases, like diabetes [22,[62][63][64][65] , chronic ethanol consumption [66][67][68] and inflammation [69] .…”
Section: Nitrergic Neuronsmentioning
confidence: 99%